A Scalable Secret Image Sharing Method Based on Discrete Wavelet Transform - Kong, Jun; Zhang, Yanfen; Meng, Xiangbo; Zheng, Ying; Lu, Yinghua (Bio-Inspired Computational Intelligence and Applications, 2007)
This paper presents a scalable secure scheme for sharing and hiding secret image. The given secret image is firstly divided into numerous non-overlapping blocks, and then transformed each block into wavelet frequency by one-level discrete wavelet transform. Second, quantization the wavelet coefficients into 256 gray level. Third, a bit-plane scanning method rearranges the gray value information of the quantized image. Four, share the rearranged image into n shadows by using multiple thresholds. Five, conceal each shadow image in R, G and B channels of the cover image, which doesn’t attract Attracters’ attention. Six, the more shadows the better quality of the retrieved secret image. The experimental results show that the retrieved secret image presents higher visual quality and the stego-images present better invisibility than traditional methods.